An investigation of radiographers' mobile phone use and the success of an awareness campaign at reducing the nosocomial infection risks. Issue 1 (February 2018) - Crofton, C.C.; Foley, S.J.
Abstract: Introduction: Mobile phone use by healthcare workers (HCWs) is widespread. Studies have shown that HCW's mobile phones can harbour pathogens associated with nosocomial infections. This study investigated whether an awareness campaign will result in an improvement in radiographers' phone and hand hygiene practices. Methods: Radiographers working in the general department of two university hospitals were invited to participate. One hospital was assigned as the experiment hospital and the other as a control. In the experiment hospital, adenosine triphosphate (ATP) testing of each participant's mobile phone determined the cleanliness of its surface. A corresponding survey was completed to determine their current practices and level of awareness. Subsequently, an infection control poster campaign took place for a one-month period, followed by re-testing. In the control hospital, the ATP testing and survey were also completed before and after a one-month period, but without a poster campaign. Results: Radiographers were generally unaware of the infection risks associated with mobile phone use with 44% of all participants never cleaning their phone. The campaign successfully improved phone hygiene frequency and method in the experiment hospital. However, it did not improve hand hygiene practices and actual phone cleanliness (mean ATP count reductions of 10% (experiment hospital) and 20% (control)). The ATP testing as a less direct form of intervention showed similar levels of success in comparison to the poster campaign. Conclusions: A multifaceted educational approach is likely to be most effective in raising awareness and changing radiographers' phone and hand hygiene practices. Highlights: 97% of participants used their mobile phone at least several times per day at work. Mobile phone disinfection was suboptimal for 66% of participants. Hand hygiene following phone use was suboptimal for 100% of participants. A poster campaign successfully improved phone hygiene practices. ATP testing successfully highlighted mobile phone contamination to participants.